2021
DOI: 10.1080/10942912.2020.1867569
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and functionality of air and spray dried egg powder: implications to improving diets

Abstract: Weak market linkages, unavailability of cold-storage, and the significant loss of eggs due to breakage and low shelf-life contribute to the unaffordability and the low consumption of eggs in low-income countries like Ethiopia. The effect of spray-and oven-drying of eggs from local (Ethiopian) and exotic (imported) chicken breeds on physical, techno-functional, and nutritional composition of egg-powders were evaluated. Exotic (n = 150) and local (n = 140) eggs were spray/oven dried. The yield, bulk-density, flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
3
19
0
1
Order By: Relevance
“…The results show that the fat content of powder milk, egg powder and milk–egg powder ranged from 26 to 42 (g 100 g −1 ) and the water content was less than 5%. According to Abreha et al 22 , the low moisture (< 5%) and water activity (a w ~ 0.4–0.5) of egg powders make unfavourable conditions for microbial growth. The fat content of powder milk (26.50 g 100 g −1 ) corresponds to the values obtained by Pugliese et al 23 and the protein content of 27.55 (g100 g −1 ) corresponds to the values obtained by Magan et al 24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the fat content of powder milk, egg powder and milk–egg powder ranged from 26 to 42 (g 100 g −1 ) and the water content was less than 5%. According to Abreha et al 22 , the low moisture (< 5%) and water activity (a w ~ 0.4–0.5) of egg powders make unfavourable conditions for microbial growth. The fat content of powder milk (26.50 g 100 g −1 ) corresponds to the values obtained by Pugliese et al 23 and the protein content of 27.55 (g100 g −1 ) corresponds to the values obtained by Magan et al 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Acidity influences the type of oxysterols formed at pH between 5.5 and 3.0, the β-isomer and is more acid labile than the α-isomer, preferentially converting into a triol by hydrolysis 25 . Abreha et al 22 showed in their study that egg powders have a low water activity of 0.4 and acidity between 7.5 and 8.5 pH.…”
Section: Resultsmentioning
confidence: 99%
“…The basal composition of the experimental diets was based on the National Research Council specifications (NRC, 1993) [13]. The dry matter (105 °C, overnight), ash (650 °C, 6 h), crude protein (nitrogen × 6.25), ether extract, and crude fiber contents of the diets and egg powder (Table 2) were determined according to the AOAC methods [14,15,16,17]. The fish were fed thrice daily throughout the study with a daily feed allowance of 3% of their body weight per day.…”
Section: Dietsmentioning
confidence: 99%
“…Oven drying: Oven drying of the edible egg and eggshell was carried out according to (Abreha et al, 2021) in a ventilated oven at 44 °C in place of 6 h. (DHG-9123A Michel, England). The dried whole egg and eggshell were permitted to cool; the flakes were bundled, pulverized using a coffee grinder (FW 100, China), and put through a sieve to card over and done with a 60 mm mesh.…”
Section: Dryingmentioning
confidence: 99%
“…In Ethiopia context, eggs are recognized by nonprofessional consumers in the class of; 'i) the smaller eggs with deep-yellow colored yolk known as Habesha (local) egg, and; ii) the larger eggs with lighter yellow yolk known as Ferengi eggs and obtained from imported breeds (exotic) egg' (Abreha et al, 2021). Despite this differentiation and consumer preference for the local breed egg, petite information exists about the difference in the nutritional and techno-functional composition of these two egg types, and how they are impacted by drying techniques and breed type variation.…”
Section: Introductionmentioning
confidence: 99%